A model for the post-Keynesian firm - Aidar, Gabriela Lima; Terra, Fábio Henrique Bittes (Brazilian Keynesian Review, 2019)
This paper aims at theoretically modelling the Post Keynesian firm. What we notice in the Post Keynesian literature is that there are several elements concerning the firm theory, however they are sparse; thereby, there is not a consolidated and summarized form of firm, in which all these relevant elements are combined to synthesize the Post Keynesian firm. But, if the Post Keynesian theory has not got a portrait of the its firm, what could mirror its constitution? To do so, this paper recalls to a firm that is already consolidated in the economic theory and that is not divergent to the Post Keynesians, the one furnished by the Resource Based View. Departing from an already available firm theory, the Resource Based View approach of the firm guides what must be looked at in order to design the synthesis of the Post Keynesian firm.